Pkb/Akt1 Mediates Wnt/GSK3β/β-Catenin Signaling-Induced Apoptosis in Human Cord Blood Stem Cells Exposed to Organophosphate Pesticide Monocrotophos - Kashyap, Mahendra P. (Mary Ann Liebert, Inc., 2013)
Inhibition mechanisms of protein kinase B (Pkb)/Akt and its consequences on related cell signaling were investigated in human umbilical cord blood stem cells (hUCBSCs) exposed to monocrotophos (MCP, an organophosphate pesticide). In silico data reveal that MCP interacts with kinase and c-terminal regulatory domains of Akt1, resulting into a total docking score of 5.2748 and also forms H-bond between its N-H and Thr-291 residue of Akt1, in addition to possessing several hydrophobic interactions. The main cause of Akt inhibition is considered to be the strong hydrogen bond between N-H and Thr-291, and hydrophobic interactions at Glu-234, and Asp-292 in the vicinity, which is usually occupied by the ribose of ATP, and interaction with residue Phe-161, thus leading to a significant conformational change in that particular portion of the protein. In silico data on Akt inhibition were confirmed by examining the downregulation of phosphorylated (Thr308/Ser493) Akt1 in MCP-exposed hUCBSCs. MCP-mediated altered levels of pAkt downstream targets viz., downregulated pGSK3β (Ser9), unchanged GSK3αβ, and upregulated levels of Bad, P(53), and caspase-9 further confirm the inhibition of pAkt. The cellular fate of such pAkt inhibition was confirmed by increased terminal deoxynucleotide transferase dUTP nick-end labeling positive cells, reduced mitochondrial membrane potential, and the activation of various MAPKs, proapoptotic markers-Bax, and caspases-9/3. Our data demonstrate that Akt1 plays a key role in MCP-induced apoptosis in hUCBSCs. We also identified that such cellular responses of human cord blood stem cells against MCP were due to strong binding and inhibition of kinase and AGC-Kinase-C terminal regulatory domains of Akt1.